Clinical characteristics and usage of statins in patients with stable ischemic heart disease referred for angiography or coronary artery bypass grafting - I.V. Shklianka; O.J. Zharinov; К.O. Mikhaliev; O.A. Epanchintseva (Кардіохірургія та інтервенційна кардіологія)
The aim – to compare the clinical characteristics and frequency of statins usage in real clinical practice in patients referred to a specialized clinic for angiography or coronary artery bypass grafting. Materials and methods. In a retrospective slice single-center study data from a primary examination of 155 patients with stable ischemic heart disease, consecutively selected for coronary artery bypass grafting surgery, were analyzed. Depending on the inclusion of statins in the list of medicinal prescriptions, patients were retrospectively divided into two groups: those who had been prescribed statins while they were initially referred to a specialized cardiac surgery center for angiography or revascularization (n = 84) and those who were not prescribed statins (n ​​= 71). Results. The studied patients’ cohort was characterized by earlier coronary events, signs of the peripheral artery atherosclerosis and other absolute indications for treatment with statins in vast majority of cases. At the same time, groups of patients who had been and had not been prescribed statins, did not differ by vast majority of demographic, clinical and instrumental characteristics, concomitant diseases and risk factors. No statin therapy was associated with higher levels of total cholesterol and interleukin-6 compared with the group of patients taking statins (total cholesterol, respectively, 4.8 versus 4.2 mmol/l (p = 0.016) and interleukin-6, respectively, 4.4 versus. 3.1 p/ml (p = 0.022)). In general, statins were prescribed in 54,2 % of patients, among them high doses – in 17 patients (20.2 %), moderate – 46 patients (54.8 %), low – 21 patients (25 %). Conclusions. The obtained data show the insufficient level of ambulatory statins usage in patients with ischemic heart disease referred for myocardial revascularization and significant discrepancy between clinical characteristics and real statins usage. Therefore, there is a great need to determine the optimal dosage, the timing of the appointment and suspension of treatment with statins in patients with stable ischemic heart disease being prepared for coronary artery bypass grafting surgery.